Directed reading thinking activity strategy: A study to enhance students’ reading comprehension - Hasanudin Hasanudin; Erpin Said; Anawia Rumalean (Qalam : Jurnal Ilmu Kependidikan, 2020)
The objective of this study was to test the strategy of the Directed Reading Thinking Activity (DRTA) in improving students' reading comprehension in the second grade of junior high school. This study used a quantitative method in the form of quasi-experimental, with a nonequivalent control group design. With the number of population was 266, the researcher took 30 samples for control and 30 samples for experiment class. The result of this study found that the value of t-test 8.233 is higher than t-table 1.699. So, the alternative hypothesis (H1) is accepted, and the null hypothesis (H0) is rejected. The calculation showed that usage Directed Reading Thinking Activity successful in improving students' reading comprehension.